Types of professionalization: Understanding contemporary organizational designs of Swiss national sport federations - Lang, G.; Schlesinger, T.; Lamprecht, M.; Ruoranen, K.; Klenk, C.; Bayle, E.; Clausen, J.; Giauque, D.; Nage, S. (Sport, Business and Management, 2018)
Purpose: The purpose of this paper is to identify types of professionalization in Swiss national sport federations (NSFs) and analyze organizational characteristics associated with specific types of professionalization. Such types reveal common patterns among the increasingly complex organizational designs of NSFs and thus contribute to the understanding of professionalization in NSFs. Design/methodology/approach: An online survey of all Swiss NSFs was conducted to identify types of professionalization in these organizations using hierarchical cluster analysis, based on a multi-dimensional framework of professionalization. Findings: The analysis revealed four types of professionalization: formalized NSFs managed by paid staff, NSFs managed by volunteers and a few paid staff off the field, NSFs with differing formalization and paid staff on the field, and moderately formalized NSFs managed by volunteers. The types differ in terms of the NSFs` organizational characteristics, in particular, size, financial resources, Olympic status, and performance. Originality/value: Applying factor and cluster analysis is a new approach to analyzing professionalization in NSFs that makes uncovering distinctive organizational patterns among a large number of NSFs possible. These results lay the foundation for understanding the professionalization of NSFs, counseling NSFs on their organizational development, and conducting future research on the design types of sport organizations.